Respuesta :
General form for squaring a binomial is [tex] (a+b)^{2} = a^{2} + 2ab + b^{2} [/tex]
In this binomial, the a is x and b is 7 so plug in and chug:
[tex] x^{2} +2(x)(7) + 7^{2} [/tex]
[tex] x^{2} + 14x + 49[/tex] - Final answer
In this binomial, the a is x and b is 7 so plug in and chug:
[tex] x^{2} +2(x)(7) + 7^{2} [/tex]
[tex] x^{2} + 14x + 49[/tex] - Final answer
ANSWER
[tex] {(x + 7)}^{2} = {x}^{2} + 14x + 49[/tex]
EXPLANATION
The given expression is
[tex] {(x + 7)}^{2} [/tex]
We can rewrite this as,
[tex] = (x + 7)(x + 7)[/tex]
Recall that,
[tex](a + b)(c + d) = ac + ad + bc + bd[/tex]
This is called the distributive property.
We apply the distributive property to get,
[tex] {(x + 7)}^{2} = {x}^{2} + 7x + 7x + {7}^{2} [/tex]
This simplifies to
[tex] {(x + 7)}^{2} = {x}^{2} + 14x + 49[/tex]
The correct answer is B.
[tex] {(x + 7)}^{2} = {x}^{2} + 14x + 49[/tex]
EXPLANATION
The given expression is
[tex] {(x + 7)}^{2} [/tex]
We can rewrite this as,
[tex] = (x + 7)(x + 7)[/tex]
Recall that,
[tex](a + b)(c + d) = ac + ad + bc + bd[/tex]
This is called the distributive property.
We apply the distributive property to get,
[tex] {(x + 7)}^{2} = {x}^{2} + 7x + 7x + {7}^{2} [/tex]
This simplifies to
[tex] {(x + 7)}^{2} = {x}^{2} + 14x + 49[/tex]
The correct answer is B.